2018
DOI: 10.4067/s0718-18762018000100105
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Shopping Consumers’ Behavior: An Exploratory Study and Review

Abstract: Mobile Technology is creating a range of tremendous opportunities and new revenue streams for businesses across industry sectors through the delivery of chargeable mobile products and services via the deployment of innovative value-added solutions that exploit the commercial benefits of mobility. To keep up with the pace of change, companies increasingly want to understand the behavioral attitude of the modern mobile consumer. The aim of this paper is to find out users' reaction towards different parameters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 94 publications
5
67
0
Order By: Relevance
“…In this paper, we examined the effect of learning costs on user intention, and to which extent this effect is mediated by perceived functional value and facilitating conditions. Indeed, the lower adoption rates of mobile payment have been reported in prior research [18] and stated to differ between countries and among diverse types of products or services which are bought using mobile payment systems [51]. The former can be explained by applying our reasoning that the marginal value is perceived differently by consumers when using mobile payment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this paper, we examined the effect of learning costs on user intention, and to which extent this effect is mediated by perceived functional value and facilitating conditions. Indeed, the lower adoption rates of mobile payment have been reported in prior research [18] and stated to differ between countries and among diverse types of products or services which are bought using mobile payment systems [51]. The former can be explained by applying our reasoning that the marginal value is perceived differently by consumers when using mobile payment.…”
Section: Discussionmentioning
confidence: 73%
“…Also, mobile payment services may be adopted differently depending on the type of product or service in question. For instance, mobile payment services are used mainly for transport in Scandinavian countries, while users in southern Europe usually pay food and clothes at stores with their mobile applications [51]. In summary, the analysis of mobile payment for specific types of products or services requires further analysis and research in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond cost savings, e-book users may use the cloud-based bookstores to collect and exhibit e-books, which offers them the benefits of movement, flexibility, and value-added functionality whenever they need to search and manipulate digital information [4]. A number of studies have found factors that encourage users to use e-books [1,[16][17][18] or, they examine how users perceive e-books in general [19]. Most of these studies adopted various theoretical perspectives, such as innovation diffusion theory [18], task-technology fit [11,16,17], technology acceptance theory [1,17,20], or expectation confirmation theory [10], to undertake their respective studies.…”
Section: Cloud-based Bookstoresmentioning
confidence: 99%
“…A number of studies have found factors that encourage users to use e-books [1,[16][17][18] or, they examine how users perceive e-books in general [19]. Most of these studies adopted various theoretical perspectives, such as innovation diffusion theory [18], task-technology fit [11,16,17], technology acceptance theory [1,17,20], or expectation confirmation theory [10], to undertake their respective studies. In [14], the authors deeply explored the diffusion of innovations theory that includes Rogers' Diffusion of Innovations curve to create innovation categories suitable for understanding e-book usage.…”
Section: Cloud-based Bookstoresmentioning
confidence: 99%
“…M-commerce is growing at 39% each year and it is estimated to exceed $31 billion dollars. 80% of global consumers are owning mobile phones, which took the attention of marketers to understand the consumer's mobile preference to provide personalized products and services to consumers (Saprikis et al, 2018).…”
Section: E-commerce Conceptmentioning
confidence: 99%